PEMANFAATAN TEKNOLOGI OLAHAN SAWI UNTUK MENINGKATKAN EKONOMI DIGITAL KELOMPOK BRASSICAN DI KAMPUNG EDUWISATA SAWI BANJARARUM: PEMANFAATAN TEKNOLOGI OLAHAN SAWI UNTUK MENINGKATKAN EKONOMI DIGITAL KELOMPOK BRASSICAN DI KAMPUNG EDUWISATA SAWI BANJARARUM - Selvia Wijaya, Elita Mega; Handayani, Sri; Rifa’i, M (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2024)
This community service activity is motivated by the great potential of mustard greens as a leading commodity in Banjararum Village, Singosari District, Malang Regency, which has not been utilized optimally. The Brassican group in Eduwisata Sawi Village has an important role in the development of mustard plant-based products, but they face obstacles in technology processing and digital marketing that can increase the economic value of the product. Therefore, this activity aims to provide training and assistance related to technological innovations in processing mustard plants into various value-added processed products, as well as improve digital marketing capabilities through e-commerce platforms. The method of implementing the activity includes several stages, namely (1) training in mustard greens processing technology into products such as mustard chips, mustard juice, and other processed products, (2) assistance in the use of digital platforms for product marketing, and (3) evaluation of the results of the application of technology and digital marketing to increase group income. This activity is carried out with a participatory approach, where group members are actively involved in each stage of training and mentoring. The results of the activity showed an increase in the ability of group members to produce various processed mustard products, as well as a significant increase in digital marketing which had a direct impact on increasing the group’s income. In addition, this activity succeeded in strengthening the position of the Brassican Group as a pioneer in the development of processed mustard products at the local and regional levels, as well as increasing the attractiveness of the Sawi Edutourism Village as an agriculture-based educational tourism destination.